Pendekatan Adaptive Reuse pada Perancangan Interior Ruang Interaktif Museum Mandala Bhakti di Semarang - Rahayu Sulistyowati; Adisti Ananda Yusuff (Journal of Innovative and Creativity, 2025)
The adaptive reuse approach is a design strategy that emphasizes the reutilization of old buildings by transforming their functions without eliminating their historical value. This strategy offers a potential solution for heritage buildings experiencing functional decline, including the Mandala Bhakti Museum in Semarang. As a military museum that houses historical collections of the Indonesian National Armed Forces (TNI), it currently faces challenges such as low visitor numbers, particularly among the younger generation, due to a lack of innovation in spatial presentation and visitor engagement. This study adopts a qualitative approach using a case study method to explore the potential of revitalizing the museum through interior design based on the adaptive reuse concept. The main focus is on developing interactive spaces that integrate educational elements, digital technology, and historical values to create immersive experiences relevant to contemporary needs. Data were collected through field observations, visual documentation, and literature studies. The findings serve as the foundation for designing interactive spaces that not only preserve the historical character of the building but also revive the museum’s appeal as an adaptive and educational public space amidst the urban development of Semarang.